Murine Fecal Microbiota Transplantation Alleviates Intestinal and Systemic Immune Responses in Campylobacter jejuni Infected Mice Harboring a Human Gut Microbiota - Heimesaat, Markus M.; Mrazek, Katharina; Bereswill, Stefan (Frontiers in Immunology, 2019)
Human campylobacteriosis constitutes a zoonotic food-borne disease and a progressively rising health burden of significant socioeconomic impact. We have recently shown that conventional mice are protected from Campylobacter jejuni infection, which was not the case for human microbiota associated (hma) mice indicating that the host-specific gut microbiota composition primarily determines susceptibity towards or resistance against C. jejuni infection. In our present preclinical intervention study we addressed whether gut microbiota changes in stably C. jejuni infected hma mice following murine fecal microbiota transplantation (mFMT) could alleviate pathogen-induced immune responses. To accomplish this, secondary abiotic C57BL/6 mice were generated by broad-spectrum antibiotic treatment, perorally reassociated with a complex human gut microbiota and challenged with C. jejuni by gavage. Seven days later C. jejuni infected hma mice were subjected to peroral mFMT on three consecutive days. Within a week post mFMT fecal pathogenic burdens had decreased by two orders of magnitude, whereas distinct changes in the gut microbiota composition with elevated numbers of lactobacilli and bifidobacteria could be assessed. In addition, mFMT resulted in less C. jejuni induced apoptotic responses in colonic epithelia, reduced numbers of macrophages and monocytes as well as of T lymphocytes in the large intestinal mucosa and lamina propria and in less distinct intestinal pro-inflammatory cytokine secretion as compared to mock challenge. Strikingly, inflammation dampening effects of mFMT were not restricted to the intestinal tract, but could also be observed systemically as indicated by elevated serum concentrations of pro-inflammatory cytokines such as TNF-α, IL-12p70 and IL-6 in C. jejuni infected hma mice of the mock, but not the mFMT cohort. In conclusion, our preclinical mFMT intervention study provides evidence that changes in the gut microbiota composition which might be achieved by pre- or probiotic formulations may effectively lower intestinal C. jejuni loads, dampen both, pathogen-induced intestinal and systemic inflammatory sequelae and may represent a useful tool to treat continuous shedding of C. jejuni by asymptomatic carriers which is critical in the context of food production, hospitalization and immunosuppression.